Odpowiedzi

2009-11-17T16:20:57+01:00
1)n²+5²= n²+25
2)9c²+2²=9c²+4
3)5²-x²=25-x²

2009-11-17T16:24:02+01:00
Ja to robie z zastosowaniem wzorów skróconego mnożenia:
(n+5)²=n²+ 2×n5+ 5²
(3c+2)²= 3c²+2×3c×2+4
(5-x)²= 25- 2×5x+x²
a bez użycia wzorów
a)= 25n²
b)9c²+4
c)25x²
Najlepsza Odpowiedź!
2009-11-17T16:27:21+01:00
(n + 5)² = (n + 5)(n + 5) = n² + 5n + 5n + 25 = n² +10n + 25

(3c + 2)² = (3c + 2)(3c + 2) = 9c² + 6c + 6c + 4 = 9c² + 12c + 4

(5 - x)² = (5 - x)(5 - x) = 25 - 5x - 5x + x² = 25 - 10x + x²

Przekształć w postaci iloczynu.

c² + 4c + 4 = (c+2)(c+2)

x² - 6x + 9 = (x-3)(x-3)

49u² - 42pu + 9p² = (7u-4p)(7u+3p)